ULTIMUM REMEDIUM AND THE LEGAL POLITICS OF TAX CRIMINAL PROSECUTION IN INDONESIA - Abduh, Arridho; Anto, Irma Romi; Abdulghani, Naser Ali (Yayasan Pendidikan Islam Almatani, 2025)
The enforcement of tax criminal law in Indonesia faces a structural dilemma between the principle of ultimum remedium, which emphasizes the recovery of state financial losses, and the tendency to apply primum remedium, which is punitive. This study uses a juridical-normative method with a statutory, conceptual, case-based, and comparative approach to analyze the normative construction of the KUP Law, law enforcement practices, and Supreme Court jurisprudence related to tax crimes. The results show that the ambiguity of the discretionary formulation of Article 44B of the KUP Law, as well as the inconsistency of the ratio decidendi in court decisions, have given rise to legal uncertainty and unequal treatment of taxpayers. As a novelty, this article deconstructs the binary paradigm of ultimum remedium–primum remedium and proposes the Integrative Justice Model as an alternative theoretical framework. This model is designed as a legal triage mechanism that classifies tax crimes based on the level of seriousness of the act and the degree of culpability (mens rea) of the perpetrator, thus allowing for proportional differentiation of settlement paths through: (1) administrative-restorative paths, (2) hybrid restorative-punitive paths, and (3) punitive-preventive paths. The Integrative Justice Model is offered as a normative solution to bridge the interests of state financial restoration with just, effective, and legal certainty-oriented criminal law enforcement.